An Unconventional Mechanistic Insight into SCF3 Formation from Difluorocarbene: Preparation of 18F‐Labeled α‐SCF3 Carbonyl Compounds. Issue 12 (14th February 2017) - Zheng, Jian; Cheng, Ran; Lin, Jin‐Hong; Yu, Dong‐Hai; Ma, Longle; Jia, Lina; Zhang, Lan; Wang, Lu; Xiao, Ji‐Chang; Liang, Steven H.
Abstract: Trifluoromethylthiolation by sulfuration of difluorocarbene with elemental sulfur is described for the first time, which overrides long‐standing trifluoromethyl anion‐based theory. Mechanistic elucidation reveals an unprecedented chemical process for the formation of thiocarbonyl fluoride and also enables transition‐metal‐mediated trifluoromethylthiolation and [ 18 F]trifluoromethylthiolation of α‐bromo carbonyl compounds with broad substrate scope and compatibility. Abstract : A trifluoromethylthio anion generated from a S8 /:CF2 /F − system occurs by sulfuration of difluorocarbene rather than capture of difluorocarbene by fluoride. This process translates well to rapid trifluoromethylthiolation and [ 18 F]trifluoromethylthiolation of α‐bromo carbonyl compounds.